Adaptation to oxidative stress at cellular and tissue level. (4th March 2022) - Akki, Rachid; Siracusa, Rosalba; Cordaro, Marika; Remigante, Alessia; Morabito, Rossana; Errami, Mohammed; Marino, Angela
Abstract: Several in vitro and in vivo investigations have already proved that cells and tissues, when pre-exposed to low oxidative stress by different stimuli such as chemical, physical agents and environmental factors, display more resistance against subsequent stronger ischaemic injuries, resulting in an adaptive response known as ischaemic preconditioning (IPC). The aim of this review is to report the most recent knowledge about the complex adaptive mechanisms, including signalling transduction pathways, antioxidant systems, apoptotic and inflammation pathways, underlying cell protection against oxidative damage. In addition, an update about in vivo adaptation strategies in response to ischaemic/reperfusion episodes and brain trauma is also given.